2018
DOI: 10.1016/j.jad.2018.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal anxiety and depression on fetal neuro-development

Abstract: Of clinical importance is the finding that although fetuses are affected by maternal mental health in general here we demonstrate, using eye-blink-rate during stimulation as measure of neuro-development, that fetuses are differentially affected by maternal anxiety and depression with anxiety increasing and depression decreasing fetal reactivity significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 48 publications
2
24
0
6
Order By: Relevance
“…3) indicates that there might be potential to use fine-grained movement analysis to highlight specific movements, such as lip parting and lip puckering, which may be predictive of fetal state. Furthermore, other specific movements (e.g., lip pull) might be influenced by maternal mental health which has previously been shown indicative of neurobehavioral development, such as increased eye-blink rate in fetuses of anxious mothers [5]. These specific movements could potentially be used as prenatal markers for adverse neurodevelopment.…”
Section: Hg Affects Fetal Movementmentioning
confidence: 98%
See 2 more Smart Citations
“…3) indicates that there might be potential to use fine-grained movement analysis to highlight specific movements, such as lip parting and lip puckering, which may be predictive of fetal state. Furthermore, other specific movements (e.g., lip pull) might be influenced by maternal mental health which has previously been shown indicative of neurobehavioral development, such as increased eye-blink rate in fetuses of anxious mothers [5]. These specific movements could potentially be used as prenatal markers for adverse neurodevelopment.…”
Section: Hg Affects Fetal Movementmentioning
confidence: 98%
“…Although the placenta selectively supplies necessary nutrients throughout pregnancy, fetal growth is most vulnerable to maternal dietary deficiencies (e.g., protein and micronutrients) during placental development early in pregnancy [3]. Not only nutritional status, but also maternal mental health (stress, anxiety and depression) has been identified as a significant prenatal factor predicting postnatal development [4,5]. The time from conception to 2 years is when individuals are most sensitive to factors leading to chronic disease in adult life [6][7][8].…”
Section: Nutritional Stress and Pregnancy Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined these movements when foetuses were stimulated cross modally with sound and light. Our rationale is twofold: (i) prior research has found that sound and light stimulation increases reactions in normally developing foetuses, and hence is an optimal condition for observing foetal facial reactions; (ii) foetal reactions to stimulation can be interpreted as precursors of neurocognitive functioning and muscle tone and, given the established neurocognitive deficits and hypotonia in PWS children, foetal reactions to stimulation are hypothesised to differ prenatally.…”
mentioning
confidence: 99%
“…The stimuli applied consisted of light and sound visible and audible to foetuses at the ages observed gestation (see for a detailed description of the stimuli and coding). The 4D ultrasound scans were then coded offline using the Fetal Observable Movement System and Coders were blind to case‐control status. Reliability tests were carried out by independent coders on 10% of observations with Cohen's Kappa mean = 0.93 (range 0.66–0.99).…”
mentioning
confidence: 99%